Impact of preoperative indocyanine green injection on intraoperative decision-making and lymph node harvest in rectal cancer surgery - Pacilli, Mario; Pavone, Giovanna; Lamanna, Ennio; Picciariello, Arcangelo; De Fazio, Michele; Ambrosi, Antonio; Tartaglia, Nicola (Frontiers in Surgery, 2025)
BackgroundReal-time fluorescence-guided surgery using intraoperative indocyanine green (ICG) has gained increasing popularity in colorectal procedures. This study aims to assess the effectiveness of ICG fluorescence imaging in enhancing the intraoperative identification of lymph nodes and in reducing the rate of anastomotic leakage.MethodsA retrospective single-center study was conducted between September 2020 and December 2024 at a tertiary colorectal cancer surgery center. Patients with rectal cancer who underwent minimally invasive anterior rectal resection were included. They were divided into two groups: Group A received both preoperative peritumoral and intraoperative intravenous ICG injections, while Group B did not receive ICG. The intraoperative and short-term outcomes, including the number of harvested lymph nodes and the rate of anastomotic leakage, were compared between the groups.ResultsA total of 40 patients (22 males) were included in the study. Operative time, hospital stay, intraoperative blood loss, and transfusion rates were similar between the two groups. Although the ICG group had a higher number of harvested lymph nodes (19 vs. 18), positive nodes, and lymph node ratio (LNR), these differences were not statistically significant on univariate analysis. Intraoperative changes were made in 30% of ICG cases to extend lymphadenectomy and in 25% to modify resection margins. Notably, no anastomotic leaks occurred in the ICG group (Group A), compared to a 10% leak rate in the control group (Group B). Linear regression analysis demonstrated that ICG use was significantly associated with increased lymph node yield (β = 3.65, p = 0.002), a higher number of positive nodes (β = 0.85, p = 0.028), and a greater LNR (β = 0.061, p = 0.034), indicating improved oncologic accuracy.ConclusionsThis study demonstrates the feasibility and safety of using ICG fluorescence imaging in minimally invasive rectal cancer surgery. Its use could enhance lymph node mapping, support faster bowel recovery, and potentially reduce the risk of anastomotic leaks.